Good art, bad art – what is a 'good' drawing?. Issue 1 (1st March 2013) - Rohr, Doris
The article addresses subjectivity in relation to assessment of drawing as fine art practice within higher education contexts. How can we measure the quality of a drawing in contemporary fine art? What standards can one take recourse to, or use, to define boundaries and definitions for excellence? The role of outsider art, and of art not produced or valorized within institutional norms, is an area of tension within academic contexts. Do we overly valorize rejection of norms and traditions, or to the contrary, do we create neo-conformism in the way we teach drawing within fine art? This article asks to reconsider aesthetics as a potential way of redressing the need to build overarching standards and measuring codes, independent from agents and institutions that have become interested parties and stake holders: the curatorial function of museum and gallery, market forces, Research Council and Arts Council. A more meaningful dialogue with different types of public needs to be sought, to redress criticism that contemporary arts practices are elitist and removed from the realities of everyday life.